Taxation of revenue derived from activities carried out by farmers in Poland - Wojciech Maruchin (Contemporary Economics, 2023)
The main aim of this study is to present the basic principles of taxing revenue derived from activities carried out by farmers in Poland, resulting from the regulations of tax law in Poland, and propose solutions concerning that law as it should stand. These are revenues derived from agricultural activities as defined in the provisions of the Polish Act on Agricultural Tax as well as in the provisions of the Polish Act on Goods and Services Tax, regardless of whether they are carried out by farmers acting as individuals or utilizing agricultural cooperatives with legal personality or commercial law companies without legal personality for their activities. This revenue is not subject to either forestry tax or income tax (only revenue from special sections of agricultural production may be subject to income tax, but this is treated as revenue generated by farmers). The rationale for the study stems from the scarcity of scientific publications on the subject - probably due to low interest among the entities conducting this type of activity. The method adopted involved the analysis of legal material and the views presented in the legal scholarship and in the case-law of administrative courts. Comparative analysis of Polish and EU law was applied. Moreover, currently applicable law was analyzed by employing a method of interpretation of both Polish and EU regulations, to the extent necessary to conduct comparative legal investigation. The particular nature of agricultural activity in Poland, dating back to the previous economic system, has influenced the decision to perform research on two levels. The first consists of the provisions of the agricultural tax law in Poland, dating back to 1984. The second level is the EU acquis, consisting in both EU legislation and Court of Justice of the European Union case-law relating to this type of activity in connection with its inclusion in the scope of value-added tax regulations. Each Member State, including Poland, is obliged to harmonize its law with the EU law in the examined scope. The results of the conducted comparative analyses indicate that identified deficiencies in the construction of the agricultural tax need to be amended.
Keywords: K34; Q14; H20; 330; agricultural activity; agricultural tax; value added tax; tax on goods and services; harmonization ofPolish tax law with EU law; Polish tax law; EU tax law